Fatal hepatic necrosis in glandular fever - Allen, U. R. (1963)
A young man of 24 developed glandular fever, became jaundiced, and died in hepatic coma. At necropsy massive necrosis of the liver was found, thus emphasizing that all grades of severity of liver damage may occur in infectious mononucleosis.